1989
DOI: 10.1021/bi00434a071
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a hydroxyl radical-induced DNA-protein crosslink involving thymine and tyrosine in nucleohistone

Abstract: Hydroxyl radical induced formation of a DNA-protein cross-link involving thymine and tyrosine in nucleohistone is described. Hydroxyl radicals were generated in N2O-saturated aqueous solution by ionizing radiation. Samples of nucleohistone were hydrolyzed with HCl and trimethylsilylated. Analysis of irradiated samples by gas chromatography-mass spectrometry with selected-ion monitoring showed the presence of a thymine-tyrosine cross-link on the basis of typical fragment ions from the previously known mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(91 citation statements)
references
References 16 publications
2
87
0
2
Order By: Relevance
“…First, the protein may be linked to the phosphodiester backbone at a nick (topo I and Pol ␤) or a double-strand break (topo II and Spo11) (1)(2)(3)(4)10). Second, the protein may be crosslinked to an oxidized base as in the case of T4-pdg, and presumably the crosslinks that are formed by ionizing radiation and oxidative stress (5,6,12,13). Third, the protein may be crosslinked to the base, as occurs with the nitrosative deamination product of guanine, oxanine, which reacts with amino groups of DNA-binding proteins (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the protein may be linked to the phosphodiester backbone at a nick (topo I and Pol ␤) or a double-strand break (topo II and Spo11) (1)(2)(3)(4)10). Second, the protein may be crosslinked to an oxidized base as in the case of T4-pdg, and presumably the crosslinks that are formed by ionizing radiation and oxidative stress (5,6,12,13). Third, the protein may be crosslinked to the base, as occurs with the nitrosative deamination product of guanine, oxanine, which reacts with amino groups of DNA-binding proteins (11).…”
Section: Discussionmentioning
confidence: 99%
“…Two potentially abundant lesions in eukaryotic cells are the amide link between Pol ␤ and 2-deoxy-ribonolactone that is generated after cleavage of an oxidized AP site by Ape1 (10) and the nitric oxide-induced deamination of guanine to yield oxanine, which reacts with the amine groups of any DNA-binding protein to form an amide bond (11). The natures of many drug-induced crosslinks can be inferred, although there are only a limited number of studies on the structures of these lesions (12,13). Similarly, there are only a few studies on the repair of these pathological DNA-protein crosslinks, and these studies have not provided a unified model.…”
mentioning
confidence: 99%
“…Gamma radiation damages DNA indirectly through the production of free radicals (23), and the conformation of DNA and DNA-protein interactions could affect the damage created by free radicals (24).…”
Section: Comparison Between Neutron and Gamma Radiation In Ras Mutatimentioning
confidence: 99%
“…Specifically, common chemotherapeutics such as nitrogen mustards, platinum compounds, and alkylnitrosoureas (3,4,8); environmental carcinogens such as formaldehyde and 1,3-butadiene (5, 9, 10); toxic metals (11)(12)(13); nitric oxide (14); free radicals (15,16); UV light (17); and ionizing radiation (6) mediate the formation of covalent DNAprotein cross-links (DPCs). 3 Mass spectrometry-based proteomic studies have identified a large number of cellular proteins that participate in DPC formation in cells treated with cross-linking agents, including DNA repair proteins, DNA polymerases, transcription factors, and structural proteins such as histones, heat shock proteins, and tubulins (3-6, 8, 10).…”
mentioning
confidence: 99%